Arrhythmogenecity and thrombogenicity of the residual left atrial appendage stump following surgical exclusion of the appendage in patients with atrial fibrillation. (4th January 2019) - Mohanty, Sanghamitra; Di Biase, Luigi; Trivedi, Chintan; Choudhury, Fahim; Della Rocca, Domenico G.; Romero, Jorge; Gianni, Carola; Sanchez, Javier; Hranitzky, Patrick; Gallinghouse, G. Joseph; Al‐Ahmad, Amin; Horton, Rodney P.; et al.
Abstract: Introduction: It is common to find residual stump after the amputation or clip exclusion of the left atrial appendage (LAA). We evaluated the arrhythmogenic and thrombogenic potential of LAA stumps in atrial fibrillation (AF) patients. Methods: Consecutive patients undergoing catheter ablation for AF recurrence with LAA stump detected at baseline transesophageal echocardiogram (TEE) were included in the analysis. Nonpulmonary vein (non‐PV) triggers were ablated based on operator's discretion. Results: A total of 213 patients with LAA stump were included in the analysis. Firing from the LAA stump was detected in 186 cases, of which 145 received stump isolation (group I) and the stump was not targeted for isolation in 41 (group II) patients. In 27 patients with no firing from the stump (group III) only non‐PV triggers from sites other than the LAA stump were targeted for ablation. At 16.7 ± 8.5 months of follow‐up, 126 (86.9%) patients from group I, eight (19.5%) from group II, and eight (33.3%) from group III remained arrhythmia‐free off antiarrhythmic drugs (AAD) ( P  < 0.001). Sixty out of 70 patients underwent redo procedure; electrical isolation of the stump and ablation of other non‐PV triggers was done in all 60 cases. At 1 year after the repeat procedure, 55 (91.7%) patients remained arrhythmia‐free off‐AAD. A total of four (1.88%) thromboembolic (TE) events reported, three of which were transient ischemic attacks and all three patients had "smoke" detected in the left atrium. Conclusion: LAA stump is arrhythmogenic and electrical isolation improves clinical outcome. TE events are rare and mostly associated with left atrial smoke in this subset of AF population.